السر المهني للعون الاقتصادي أمام مجلس المنافسة: بين متطلبات الحماية وحتمية الإفصاح - بوعجاجة, منال; حساين, سامية (University of Eloued جامعة الوادي, 2020)
حاول المشرع الجزائري الموازنة بين حماية المصلحة العامة والمصلحة الخاصة، حيث عزز صلاحية مجلس المنافسة في الإطلاع على مختلف الوثائق والمستندات دون الاحتجاج بالسر المهني، فكرس حق العون الاقتصادي في حماية سره أمام نفس الهيئة، من خلال منحه إمكانية تفعيل هذا الحق بنفسه قبل تبليغ المآخذ أو عن طريق السحب التلقائي للوثائق السرية من طرف رئيس المجلس. كما يلتزم العون بالإفصاح عن هذه الأسرار أمام مجلس المنافسة تكريسا لحق الإطلاع الممنوح قانونا لهيئة التحقيق، وهيئة الحكم، وهيئة الدفاع على مستوى المجلس، ذلك أن قيام هذا الحق له تأثير على حماية السر المهني، كونه يقيد الحق في السرية أثناء مرحلتي التحقيق وسير الجلسات. The Algerian legislator has tried to balance the protection of the public interest and the private interest. He strengthened the authority of the as the competition council to review various documents without invoking the professional secret. He devoted the right to help protect its professional secret before the same body by giving it the ability to activate this The right of economic agent to protect their secret before the same body, by granting them the possibility to activate this right on their own before notifying the recipient or by automatic withdrawal of confidential documents by the president of the council. The agent is also obliged to disclose these secret before the competition council in order to dedicate the right of access legally granted to the investigation authority, the governing body, and the defense body at the council level, since the establishment of this right has an impact on the protection of professional secret, as it restricts the right to confidentiality during the investigation and the course of hearing.
مجلد11، عدد2
Keywords: السر المهني ; العون الاقتصادي ; الحماية ; مجلس المنافسة ; الإفصاح ; المصلحة العامة ; المصلحة الخاصة; professional secret ; economic agent ; protection ; competition council ; disclosure ; public interest ; private interest